Nitric Oxide Synthase Inhibitor Attenuates the Effects of Repeated Restraint Stress on Synaptic Transmission in the Paraventricular Nucleus of the Rat Hypothalamus - Kusek, Magdalena; Tokarska, Anna; Siwiec, Marcin; Gadek-Michalska, Anna; Szewczyk, Bernadeta; Hess, Grzegorz; Tokarski, Krzysztof (Frontiers in Cellular Neuroscience, 2017)
Corticotropin-releasing hormone (CRH)-synthesizing parvocellular neuroendocrine cells (PNCs) of the hypothalamic paraventricular nucleus (PVN) play a key role in the activation of the hypothalamic-pituitary-adrenocortical (HPA) axis. Several studies have demonstrated that synaptic inputs to these cells may undergo stress-related enhancement but, on the other hand, it has been reported that exposition to the same stressor for prolonged time periods may induce a progressive reduction in the response of the HPA axis to homotypic stressors. In the present study rats were subjected to 10 min restraint sessions, repeated twice daily for 3 or 7 days. Miniature excitatory and inhibitory postsynaptic currents (mEPSCs and mIPSCs) were then recorded from PNCs in ex vivo hypothalamic slice preparations obtained 24 h after the last restraint. Restraint stress repeated over 3 days resulted in increased mean frequency and decreased rise time and decay time constant of mEPSCs, accompanied by a decrease in the excitability of PNCs, however, no such changes were evident in slices obtained from rats subjected to restraint over 7 days. There were no changes in mIPSCs after repeated restraint. Administration of the unspecific nitric oxide synthase (NOS) blocker Nω-Nitro-L-arginine (L-NNA) before each restraint, repeated over 3 days, prevented the occurrence of an increase in mEPSC frequency. However, animals receiving L-NNA and subjected to repeated restraint had similar changes in PNCs membrane excitability and mEPSC kinetics as stressed rats not receiving L-NNA. Comparison of the effects of a single 10 min restraint session followed by either an immediate or delayed (24 h) decapitation revealed an increase in the mean mEPSC frequency and a decrease in the mean mIPSC frequency in slices prepared immediately after restraint, with no apparent effects when slice preparation was delayed by 24 h. These results demonstrate that restraint, lasting 10 min and repeated twice daily for 3 days, induces a selective and long-lasting enhancement of excitatory synaptic input onto PNCs, partially by a NOS-dependent mechanism, and reduces PNC excitability, whereas prolongation of repeated stress for up to 7 days results in an adaptation.